Oropharyngeal swallowing in chronic renal failure - Pinto, Aline Rodrigues; da Silva, Roberta Gonçalves [UNESP]; Pinato, Luciana [UNESP] (FapUNIFESP (SciELO), 2016)
Objective: To characterize the oropharyngeal swallowing profile of patients with chronic renal failure. Methods: A cross-sectional clinical study involving 20 adults diagnosed with chronic renal failure in hospital stay was conducted. The evaluation of swallowing was performed by videofluoroscopy, and characterization of findings was based on effectiveness and safety parameters. Functional Oral Intake Scale (FOIS) was also applied. Results: On videofluoroscopy, 16 patients presented changes in oral and pharyngeal patterns, three individuals presented impairment at the pharyngeal phase, and only one individual presented changes only at the oral phase of swallowing. Furthermore, videofluoroscopy showed penetration and tracheal aspiration in 30% of the sample. Before the videofluoroscopy, four individuals (20%) were at level 5 of FOIS scale, whereas 16 individuals (80%) were at level 7. After adjustments of the oral diet consistency because of safety and swallowing effectiveness, FOIS classification was six individuals at level 1, seven at level 4, four at level 5, and three at level 6. Conclusion: The characterization of oropharyngeal swallowing profile in chronic renal patients showed abnormalities at oral and pharyngeal phase, including penetration and tracheal aspiration, which requires oral intake changes.
Keywords: Renal Failure; Speech-Language and Hearing; Swallowing Disorders